The impact of digital economy on green development in China - Zhang, Zhi; Fu, Wei Kang; Ma, Li (Frontiers in Environmental Science, 2022)
With the huge dividends released by the vigorous development of the digital economy, China urgently demand a major strategic transformation from extensive development to green development. The 14th five-year plan period will require China's green development to firmly create new advantages in the growth of the digital economy. In order to investigate the impact of the digital economy on the green economy, this paper has utilized a panel data model to analyze data from 30 Chinese provinces between 2015 and 2019. Findings from the research have suggested that the digital economy is helpful for advancing the green economy, with the eastern region having a bigger influence than the central region and the center region having a greater influence than the western region. Industrial structure and technological innovation are important channels for digital economy to promote green development. According to the aforementioned conclusions, we have proposed the following suggestion: China should actively advance the digital economy, encourage regional coordination in growth, continuously improve the industrial structure and boost technical innovation.